Future Directions for Personality Research: Contributing New Insights to the Understanding of Animal Behavior - Vanessa Wilson; Anja Guenther; Øyvind Øverli; Martin W. Seltmann; Drew Altschul (MDPI AG, 2022)
As part of the European Conference on Behavioral Biology 2018, we organized a symposium entitled, “Animal personality: providing new insights into behavior?” The aims of this symposium were to address current research in the personality field, spanning both behavioral ecology and psychology, to highlight the future directions for this research, and to consider whether differential approaches to studying behavior contribute something new to the understanding of animal behavior. In this paper, we discuss the study of endocrinology and ontogeny in understanding how behavioral variation is generated and maintained, despite selection pressures assumed to reduce this variation. We consider the potential mechanisms that could link certain traits to fitness outcomes through longevity and cognition. We also address the role of individual differences in stress coping, mortality, and health risk, and how the study of these relationships could be applied to improve animal welfare. From the insights provided by these topics, we assert that studying individual differences through the lens of personality has provided new directions in behavioral research, and we encourage further research in these directions, across this interdisciplinary field.